Assessing the impact of agricultural policies on producers and consumers in selected OECS countries - Antoine, Patrick A. (IICA BridgetownBB, 1994)
Focuses on the OECS member countries of: Dominica, Grenada, St. Vincent and the Grenadines, St. Lucia, St. Kitts-Nevis and Antigua and Barbuda. Identifies the major policy measures adopted by the respective governments toward their agricultural sector over the 1989-93 period. Assesses the effect of these policies in terms of their aggregate impact on the income of producers and the welfare of consumers of the crops studied, as well as the extent of transfer payments resulting from such policies. Seeks to determine the extent of protection and the disincentive to production resulting from the policies introduced.